Scan, Pay, and Loyal : The Influence of QRIS on Customer Loyalty with the Mediation of Satisfaction and Moderation of Service Quality - Ganang Eko Widianto; Muryati Muryati; Survival Survival (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2025)
This study explores the impact of the Quick Response Code Indonesian Standard (QRIS) on customer loyalty by examining the mediating role of customer satisfaction and the moderating role of service quality. Using a quantitative approach, data were collected from 76 QRIS users at PT. Bank Pembangunan Daerah Banten (Perseroda) Tbk, Surabaya Branch. The analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The findings reveal that the implementation of QRIS significantly enhances customer satisfaction and customer loyalty. Customer satisfaction partially mediates the relationship between QRIS and loyalty, indicating that QRIS contributes to loyalty by improving the customer experience. Moreover, service quality strengthens the influence of QRIS on loyalty, serving as a pure moderator in the model. These results suggest that digital payment innovation alone is not sufficient to build loyalty; it must be supported by consistent and high-quality service delivery. The study provides practical insights for regional banks seeking to optimize QR-based services as part of their digital transformation and customer retention strategies.